Practical Paths for Integrating Excellent Traditional Chinese Culture into Labor Education for College Students - Luo, Dan; Xu, Xiaoliang (Journal of Research in Vocational Education, 2025)
Currently, labor education for college students faces challenges such as insufficient ideological guidance, a weak teaching staff, and a single educational approach. Excellent traditional Chinese culture is rich in labor education resources. It not only injects vitality into the high - quality development of labor education in colleges and universities but also helps to inherit excellent traditional culture, enhancing college students' sense of national identity and cultural confidence. Traditional culture and labor education are highly compatible in nature, guiding students to cultivate excellent labor qualities and understand the value of labor. Colleges and universities should fully draw on the labor - education elements in traditional culture. By making efforts in optimizing the content of labor education, strengthening ideological guidance, building a professional teaching staff, and innovating educational approaches, they can promote the in - depth practice of labor education, laying a solid foundation for cultivating socialist builders and successors who are well - developed morally, intellectually, physically, aesthetically, and in terms of labor.